2016
DOI: 10.1053/j.jvca.2016.03.148
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasively Measured Hemoglobin Concentration Reflects Arterial Hemoglobin Concentration Before but Not After Cardiopulmonary Bypass in Patients Undergoing Coronary Artery or Valve Surgery

Abstract: Objective This study compared non-invasively measured hemoglobin and arterial hemoglobin before and after cardiopulmonary bypass in patients undergoing coronary artery or valve surgery. Design Observational study with retrospective data analysis. Setting Veterans Affairs hospital. Participants Thirty-five men. Interventions None. Measurements and Main Results We compared hemoglobin values measured non-invasively by co-oximetry (Radical-7 Pulse CO-Oximeter; Masimo, Irvine, CA) to corresponding arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The accurate and rapid measurement of hemoglobin concentration is crucial during the decision-making process for fluid and transfusion therapy in complicated surgical procedures. Several articles have discussed the accuracy of Radical-7™ Pulse CO-Oximeter [1118]; however, the lack of statistical agreement renders the clinical applicability of this method debatable. In our consideration, the ability of one device to provide helpful measurement data may prove valuable for monitoring during complicated surgical procedures as well as critical populations.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate and rapid measurement of hemoglobin concentration is crucial during the decision-making process for fluid and transfusion therapy in complicated surgical procedures. Several articles have discussed the accuracy of Radical-7™ Pulse CO-Oximeter [1118]; however, the lack of statistical agreement renders the clinical applicability of this method debatable. In our consideration, the ability of one device to provide helpful measurement data may prove valuable for monitoring during complicated surgical procedures as well as critical populations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated the unreliability of Masimo hemoglobin measurement and go in hand with Khalafallah et al [25] who reported that SpHb may enable prompt routine preoperative anemia management, but its precision was lower than expected and Galvagno et al [26] also found noninvasive SpHb monitoring did not enhance the ability to predict the need for blood transfusion. Recently, Riess & Pagel [27] observed a lack of precision with noninvasive Hb Data are presented as mean ± SD; Group NA: received normotensive anesthesia; Group HA: received hypotensive anesthesia; SBP: Systolic blood pressure, DBP: Diastolic blood pressure, MAP: Mean arterial pressure; HR: Heart rate; PO: Postoperative; NS: Non significant difference; p < 0.05: significant difference Table 2 Regional cerebral and peripheral arterial blood oxygen saturation in patients of both groups. Peripheral arterial blood oxygen saturation; rSO 2 : regional cerebral oxygen saturation; ΔSpO 2 : difference between peripheral and regional cerebral oxygen saturation; P value: P value of significance of difference between both groups; NS: Non-significant difference Data are presented as mean ± SD; Group NA: received normotensive anesthesia; Group HA: received hypotensive anesthesia; PO: Postoperative; ΔPVI: change of Pleth variability index; * : indicates significant difference versus preoperative measurement; P value: P value of significance of difference between both groups; NS: Non-significant difference; p < 0.05: significant difference measurement, especially after cardiopulmonary bypass.…”
Section: Resultsmentioning
confidence: 99%
“…Our study has some limitations: (a) It was conducted at a single center; (b) we did not evaluate the accuracy of Masimo oximeter after cardiopulmonary bypass; however, a previous study in adult cardiac patients undergoing coronary artery or valve surgery showed that the accuracy Sp‐Hb worsened after the cardiopulmonary bypass 17 …”
Section: Discussionmentioning
confidence: 98%